PENGARUH KREATIVITAS BERWIRAUSAHA, PRESTASI BELAJAR DAN EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Maria Elen; Rusno Rusno; Udik Yudiono (Jurnal Riset Pendidikan Ekonomi, 2018)
The purpose of the study was to reveal the effect of entrepreneurial creativity, learning achievement and self-efficacy on the interests of entrepreneurship in economic education students. Research using a quantitative approach to the type of research explanatory research. The population is 105 students. A sample of 58 students was determined using proportional random sampling. Data collection techniques using questionnaires and documentation. Based on the results of the analysis, several conclusions can be drawn including: there is an influence of entrepreneurial creativity, learning achievement and self-efficacy simultaneously have a positive effect on student interest in entrepreneurship seen from the F test with a significant value of 000 <0.05. Entrepreneurial creativity has a positive influence on students' entrepreneurial interest seen from the F test with a significant value of 0.035 <0.05. Learning achievement has a positive influence on students' interest in entrepreneurship from the F test with a significant value of 0.020 <0.05. self-efficacy has a positive effect on the entrepreneurial interest in entrepreneurship seen from the F test with a significance of 0.008 <0.05.